Cangrelor in combination with ticagrelor provides consistent and potent P2Y12-inhibition during and after primary percutaneous coronary intervention in real-world patients with ST-segment-elevation myocardial infarction. (19th May 2017) - Mohammad, Moman A.; Andell, Pontus; Koul, Sasha; James, Stefan; Scherstén, Fredrik; Götberg, Matthias; Erlinge, David
Abstract: Patients pretreated with ticagrelor with less than 1 hour from percutaneous coronary intervention (PCI) or receiving ticagrelor in cath lab were prospectively included and received cangrelor. Cangrelor was infused for 2 hours and platelet function was assessed as P2Y12 reactivity units (PRU) with the VerifyNow P2Y12 function assay before start of infusion, 15 min after the start of infusion, and 30 min after the end of infusion. A total of n = 32 patients with an average age of 68 (±13) years with n = 22 (69%) males were included. The level of P2Y12 inhibition before cangrelor infusion was started was 249 PRU (IQR 221–271). After 15 min of cangrelor infusion the P2Y12 reactivity was markedly decreased to 71 PRU (IQR 52–104, p < 0.001). At 30 min after end of infusion PRU remained within the therapeutic range, 89 PRU (IQR 50–178; p < 0.001 for comparison with preinfusion) with only n = 4 (12.5%) patients with PRU >225. Results were consistent between patients receiving ticagrelor prehospital or in the cath lab and no statistical differences in PRU were noted between the two groups in any of the three measurements. In conclusion, cangrelor in combination with ticagrelor results in consistent and strong P2Y12 inhibition during and after infusion and cangrelor may bridge the gap until oral P2Y12 inhibitors achieve effect in real-world STEMI patients undergoing primary PCI.